The address : a novel - Davis, Fiona, 1966- (New York : Dutton, 2017)
"After a failed apprenticeship, working her way up to head housekeeper of a posh London hotel is more than Sara Smythe ever thought she'd make of herself. But when a chance encounter with Theodore Camden, one of the architects of the grand New York apartment house The Dakota, leads to a job offer, her world is suddenly awash in possibility--no mean feat for a servant in 1884. In 1985, Bailey Camden is desperate for new opportunities. Two generations ago, Bailey's grandfather was the ward of famed architect Theodore Camden. But the absence of a genetic connection means Bailey won't see a dime of the Camden family's substantial estate. Instead, her "cousin" Melinda--Camden's biological great-granddaughter--will inherit almost everything. So when Melinda offers to let Bailey oversee the renovation of her lavish Dakota apartment, Bailey jumps at the chance. But a building with a history as rich--and often tragic--as The Dakota's can't hold its secrets forever, and what Bailey discovers in its basement could turn everything she thought she knew about Theodore Camden--and the woman who killed him--on its head."--
Keywords: Dakota (Apartment House : New York, N.Y.) -- Fiction; Social classes -- New York (State) -- New York -- Fiction; Hotel management -- New York (State) -- New York -- Fiction; Interior decorators -- Fiction